2020
DOI: 10.1177/8755122520962859
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Dosing for the Treatment of Alcohol-Induced Wernicke’s Encephalopathy: A Review of the Literature

Abstract: Objective: To determine the most appropriate thiamine replacement regimen by evaluating safety and efficacy of the drug specific to alcohol-induced Wernicke’s encephalopathy (WE). Data Sources: A comprehensive literature search was conducted using PubMed, MEDLINE, Scopus, and ProQuest between January and August 2020 using the following keyword and Boolean search terminology: “thiamine” AND “alcohol” AND (encephalopathy OR korsakoff). Study Selection and Data Extraction: Randomized control trials; prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(58 reference statements)
1
8
0
1
Order By: Relevance
“…The results of this study showed no clear benefit of high dose thiamine over intermediate or lower doses of thiamine for the treatment and prevention of cognitive and neurological abnormalities related to WE (synonymous with acute WKS) over the time interval examined. In the absence of conclusive evidence for the superiority of high dose thiamine, these findings support a recommendation that treatment of alcohol‐induced WE should be patient‐specific (Smith et al, 2020) and include an investigation of other confounding comorbidities that may impact thiamine replacement (e.g., hypomagnesemia, sepsis, or other metabolic disturbance).…”
Section: Discussionsupporting
confidence: 58%
“…The results of this study showed no clear benefit of high dose thiamine over intermediate or lower doses of thiamine for the treatment and prevention of cognitive and neurological abnormalities related to WE (synonymous with acute WKS) over the time interval examined. In the absence of conclusive evidence for the superiority of high dose thiamine, these findings support a recommendation that treatment of alcohol‐induced WE should be patient‐specific (Smith et al, 2020) and include an investigation of other confounding comorbidities that may impact thiamine replacement (e.g., hypomagnesemia, sepsis, or other metabolic disturbance).…”
Section: Discussionsupporting
confidence: 58%
“…Intravenous isotonic crystalloid fluids can be administered to patients with symptoms of volume depletion or hypotension [ 19 ]. Parenteral thiamine should be administered to all comatose patients due to ethanol intoxication in order to prevent or treat Wernicke's encephalopathy (usual doses in prevention ranging from 100 mg to 250 mg or higher in established encephalopathy) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once a diagnosis of Wernicke encephalopathy is suspected, it is advisable to administer thiamine as early as possible to prevent permanent neurological damage[ 20 ]. Although there are no published guidelines for the treatment of Wernicke encephalopathy in non-alcoholics patients, intravenous thiamine supplementation in the acute stage is currently recommended.…”
Section: Discussionmentioning
confidence: 99%